Gangguan Hutan di KPH Kuningan Divisi Regional Jawa Barat dan Banten - Ati Dwi Nurhayati; Liana Arhami (Jurnal Silvikultur Tropika, 2019)
Forest protection is an effort to prevent and control the destruction of forests, forest areas, and forest products caused by human actions, livestock, fires, pests and diseases. The aims of this research are to identify the types of forest disturbance especially those caused by humans and physically, analyze the factors causing forest disturbance, and analyze efforts to control forest disturbance at KPH Kuningan. Forest disturbances that occurred in the KPH Kuningan during 2010-2014 included: timber theft, forest fires, forest encroachment, and natural disasters. The background of forest disturbance in the Kuningan KPH is mainly due to the socio-economic conditions of the community around the forest that are still low. Strategic actions taken to prevent forest disturbance at the KPH Kuningan are to take pre-emptive actions in the form of counseling and establish good relations between officers and the community through social communication and Community Based Forest Management (PHBM), preventive actions in the form of patrols and safeguards against forest potential, and repressive actions in the form of legal remedies against the perpetrators. Key words: cause of forest disturbance, type of forest disturbance, forest disturbance control